A Depiction of Raden Joko Kaiman as a Superhero Using Barthes’ Semiotics - Chusni Hadiati; Nadia Gitya Yulianita (Bina Nusantara University, 2021)
The research tried to reveal the denotative and connotative meaning of Raden Joko Kaiman in Banyumas culture. Historically, Banyumas regency was founded by Raden Joko Kaiman in 1582. As the founding father of Banyumas regency, Raden Joko Kaiman could be semiotically interpreted as a superhero in the context of Banyumas. Based on Barthes, anything could be a sign. Raden Joko Kaiman in Barthes’ semiotic perspective could function as a sign since this figure could have both denotative and connotative meanings. Barthes’ semiotic theory investigated the process of reading signs and their interpretation by different cultures or societies. Barthes considered sign as both signifier the physical form of the sign as people perceived it through their sense and signified the interpreted meaning. The research applied a qualitative method since it collected reliable data and information through reading, comparing, and analyzing text by relating them to Banyumas context. There are four denotative meanings carried by this sign, namely, the son of Raden Harya Banyak Sosro, the godson of Kiai Mranggi, the son-in-law of Adipati Wargautama, and being Adipati Mrapat. Connotatively, Raden Joko Kaiman is interpreted as courage, strong moral codes, tolerance towards pain, and a great sense of responsibility.